2010
DOI: 10.1021/nn1010396
|View full text |Cite
|
Sign up to set email alerts
|

Dye-Sensitized Solar Cells Employing a Single Film of Mesoporous TiO2 Beads Achieve Power Conversion Efficiencies Over 10%

Abstract: Dye-sensitized solar cells employing mesoporous TiO(2) beads have demonstrated longer electron diffusion lengths and extended electron lifetimes over Degussa P25 titania electrodes due to the well interconnected, densely packed nanocrystalline TiO(2) particles inside the beads. Careful selection of the dye to match the dye photon absorption characteristics with the light scattering properties of the beads have improved the light harvesting and conversion efficiency of the bead electrode in the dye-sensitized s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
337
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 418 publications
(340 citation statements)
references
References 16 publications
3
337
0
Order By: Relevance
“…The reduction of particles dimensionality offers faster electron transport when the photoanode is composed of vertically aligned nanowires or nanotubes [63][64][65][66][67][68][69][70][71]. The synthesis of TiO 2 beads leads to the most spectacular improvements resulting from the excellent particles interconnections, shortened mass transport pathways into the mesopores, and combination of light scattering ability and high surface area offering improved light confining properties of the photoanode [16,[72][73][74]. Remarkable efficiencies exceeding 11% (A.M. 1.5 G) were obtained on optimized beads in combination with high molar extinction coefficient C101 or C106 ruthenium dyes.…”
Section: Dye-sensitized Solar Cells Principle: Role and Progress In Tmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction of particles dimensionality offers faster electron transport when the photoanode is composed of vertically aligned nanowires or nanotubes [63][64][65][66][67][68][69][70][71]. The synthesis of TiO 2 beads leads to the most spectacular improvements resulting from the excellent particles interconnections, shortened mass transport pathways into the mesopores, and combination of light scattering ability and high surface area offering improved light confining properties of the photoanode [16,[72][73][74]. Remarkable efficiencies exceeding 11% (A.M. 1.5 G) were obtained on optimized beads in combination with high molar extinction coefficient C101 or C106 ruthenium dyes.…”
Section: Dye-sensitized Solar Cells Principle: Role and Progress In Tmentioning
confidence: 99%
“…Rapidly passing the threshold of 10% power conversion efficiency (PCE) in 1993 [10], despite endless efforts on material development, the efficiency had stagnated for a long time in the range of 11.0-11.5% [11][12][13][14][15][16] before scoring three new subsequent records, first 12.3% and 13.0% under A.M. 1.5 G conditions (100 mW/cm 2 ) using organic dye molecules in association with a stronger oxidant redox active cobalt polypyridyl complex [17,18]. More recently, certified 14.1% and even certified 17.9% PCE have been achieved by replacing the dye with a hybrid organic/inorganic lead halide perovskite absorber and the liquid electrolyte by a solid hole transporting material (HTM) [19,20] giving birth to a new technology called perovskite solar cells, for which progresses are remarkably fast.…”
Section: Introductionmentioning
confidence: 99%
“…This feature is derogated by reducing film thickness in thin-film solar cells such as dye sensitized solar cell (DSSC); therefore, many approaches are made to improve it. For example, porous active layer with high surface area [1][2][3], hierarchically nanostructures as photoanode [4][5][6], scattering layers on the top of active film [7][8][9], plasmonic photoanodes [10][11][12] and photonic crystal photoanodes [13][14][15] have been applied for changing the optical design of the DSSC to optimize its light absorbance. Since the mentioned approaches have some limitations like high reflectance loss and low dye adsorption, researchers are still extensively eager to explore the new light trapping structures as photoanode.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] It has become a focus recently that looking for alternative metal oxide semiconductors with wide band gap and good photoelectrochemical properties. [7][8][9][10] ZnO nanostructures for DSC applications has shown that they can offer large specific surface areas with well-controlled morphologies, direct electron pathways with much higher electron mobility, and also can reduce the combination rate when the surface defects are properly controlled. [11][12][13] Tin oxide (SnO 2 ) as a promising alternative semiconductor has many advantages for DSCs: (1) good electron mobility, indicating electron transport fast in photoanodes and (2) large band gap (3.6 eV) and more-negative conduction band minimum, which can enhance the light harvesting in the near-infrared spectral region when combined with small band gap sensitizer.…”
Section: Introductionmentioning
confidence: 99%